Phase I Trial of Repeated Intrathecal Autologous Bone Marrow-Derived Mesenchymal Stromal Cells in Amyotrophic Lateral Sclerosis - Oh, Ki-Wook (Stem Cells Transl Med, 2015)
Stem cell therapy is an emerging alternative therapeutic or disease-modifying strategy for amyotrophic lateral sclerosis (ALS). The aim of this open-label phase I clinical trial was to evaluate the safety of two repeated intrathecal injections of autologous bone marrow (BM)-derived mesenchymal stromal cells (MSCs) in ALS patients. Eight patients with definite or probable ALS were enrolled. After a 3-month lead-in period, autologous MSCs were isolated two times from the BM at an interval of 26 days and were then expanded in vitro for 28 days and suspended in autologous cerebrospinal fluid. Of the 8 patients, 7 received 2 intrathecal injections of autologous MSCs (1 × 10(6) cells per kg) 26 days apart. Clinical or laboratory measurements were recorded to evaluate the safety 12 months after the first MSC injection. The ALS Functional Rating Scale-Revised (ALSFRS-R), the Appel ALS score, and forced vital capacity were used to evaluate the patients’ disease status. One patient died before treatment and was withdrawn from the study. With the exception of that patient, no serious adverse events were observed during the 12-month follow-up period. Most of the adverse events were self-limited or subsided after supportive treatment within 4 days. Decline in the ALSFRS-R score was not accelerated during the 6-month follow-up period. Two repeated intrathecal injections of autologous MSCs were safe and feasible throughout the duration of the 12-month follow-up period. SIGNIFICANCE: Stem cell therapy is an emerging alternative therapeutic or disease-modifying strategy for amyotrophic lateral sclerosis (ALS). To the authors' best knowledge, there are no clinical trials to evaluate the safety of repeated intrathecal injections of autologous bone marrow mesenchymal stromal cells in ALS. After the clinical trial (phase I/II) was conducted, the stem cell (HYNR-CS, NEURONATA-R) was included in the revision of the regulations on orphan drug designation (number 160; December 31, 2013) and approved as a New Drug Application (Department of Cell and Gene Therapy 233; July 30, 2014) by the Korean Food and Drug Administration. The phase II trial is expected to be reported later.